Term alpaca placenta glycosylation profile and its correlation with pregnancy maintenance and fetal survival - Navarrete Zamora, Miluska Beatriz; Silva, Thamires Santos da; Silva, Mônica Duarte da; Almeida, Gustavo Henrique Doná Rodrigues; Silva-Júnior, Leandro Norberto da; Horvath-Pereira, Bianca de Oliveira; Baracho Hill, Amanda Trindade; Acuña, Francisco; Carreira, Ana Claudia Oliveira; Barreto, Rodrigo da Silva Nunes; Sato, Alberto Sato; Miglino, Maria Angélica (Frontiers in Cell and Developmental Biology, 2023)
Alpaca is a South American camelid, mainly located in Peruvian highlands, where oxygen concentration and atmosphere pressure are very low. Due to this fact, the gestational physiology has adapted to preserve the concept and the mother’s health. In this context, several cellular and molecular features perform an essential role during and at the end of the gestation. Structural carbohydrates acts on maternal-fetal communication, recognizes exogenous molecules and contribute to placental barrier selectivity. Therefore, this study aimed to characterize the structural carbohydrates profile that are present in the term alpaca placenta, kept in their natural habitat, around 4,000 heights. For this propose, 12 term alpaca placentas were collected, material obtained at the time of birth of camelids raised naturally in the Peruvian highlands, in Cusco region. All placenta samples were processed for histological analysis. A lectin histochemical investigation was performed using 13 biotinylated lectins, being able to determine the carbohydrates location and their intensity in a semi quantitative scale. Our results demonstrated that term gestation, the epitheliochorial alpaca placenta shows a high presence of carbohydrates, mainly glucose, α-linked mannose, N-Acetil glucosamine β (GlcNAc), Galactose (αGal) and N-Acetil galactosamine α (GalNAc), present in the trophoblast, amnion epithelium and mesenchyme, as well as the presence of sialic acid residues and low affinity for fucose. In fetal blood capillaries, the presence of bi and tri-antennary complex structures and α-linked mannose were predominated. In conclusion, we characterized the glycosylation profile in term alpaca placenta. Based on our data, compared to those reported in the bibliography, we suggest that these carbohydrates could participate in the labor of these animals that survive in Peruvian extreme environments.